The Concept of Ulul Albab in Tafsir Ibn Kaṡir: Its Relevance and Implications for Developing Students’ Critical and Creative Character - Fadllurrahman Fadllurrahman; Nahriyah Harahap; Musthofa Musthofa; Arizqi Ihsan Pratama; Rio Nandes (Mauriduna : Journal of Islamic Studies, 2025)
This article aims to explore the relevance of Ulul Albab values to the formation of students' critical and creative character, as well as how these values can be integrated into the educational curriculum as a strategy against hoaxes and misinformation. The research method used is a qualitative method with a descriptive approach. The data source comes from documents relevant to the study. Data collection techniques use documentation techniques and data analysts use document analysis techniques and are discussed in a descriptive analysis. The findings of this study The concept of Ulul Albab in the tafsir of Ibn Kaṡir is not only an invitation to reflective thinking, but also a methodological offer for the world of modern education. In the midst of a flood of information, reflective, critical, and creative characters are the most powerful shield to deal with hoaxes and misinformation. Integrating these values into the curriculum is not only relevant, but also urgent—as part of building a spiritually and intellectually enlightened generation. The implication of this study is the application of learning syntax by focusing more on reflection sessions as an effort to internalize the values of ulul albab characters to students.